OPEN REDUCTION AND INTERNAL FIXATION WITH LINEAR LOCKING COMPRESSION PLATES FOR THE STABILISATION OF UNSTABLE DIAPHYSEAL FRACTURE OF FEMUR IN DOGS - R. Ramesh; S. Ayyappan; R. Jayaprakash; Geetha Ramesh (Indian Journal of Veterinary and Animal Sciences Research, 2024)
Six dogs with unstable diaphyseal fracture of femur of different breeds of either sex and bodyweight ranging from 10 to 30 kg presented to the Small Animal Orthopedic Unit of the Madras Veterinary College Teaching Hospital, over a period of two years underwent fracture fixation with latest technique of linear locking compression plates. Different sizes and length of new generation locking plate system were used for different configuration of unstable fracture of femur. The post operative assessment of fracture healing was evaluated by radiographs at different intervals and estimation of bone specific serum alkaline phosphatase enzyme by fluorimetric methods. In the present study, the locking compression plating technique provided adequate apposition, stable fixation and promoted early weight bearing of traumatized limb. The locking plate system had a unique combi hole design in a single implant and enabled to select the function best suited for the fracture configuration to achieve the most stable fixation. The locking plate system acted as a single beam construct which increased the stiffness of the implant and was found appropriate in management of unstable or comminuted diaphyseal fracture of femur in dogs.